Assessing the Impact of Antenatal Oral Health Integration and Measuring Knowledge Gains through Educational Interventions: A Knowledge Enhancement Study - Natasha Gambhir; Nidhi Gupta; Divya Singh; Priyanka Sachdeva; Sonam Yadav (Journal of South Asian Association of Pediatric Dentistry)
The study highlights the critical role of maternal oral health in ensuring the well-being of newborns. Poor oral hygiene during pregnancy can lead to adverse outcomes, including low birth weight and premature births, as well as increase the risk of transmitting dental caries-causing bacteria to infants. The study was conducted at Santosh Hospital, Ghaziabad, and included 265 pregnant women, who were evaluated on their awareness of oral health during pregnancy. Three educational methods—colored printed posters, WhatsApp reminder messages, and one-on-one counseling—were employed to raise awareness. The results showed that one-on-one counseling was the most effective intervention, significantly improving knowledge levels (p = 0.001), followed by posters and WhatsApp messages. These findings emphasize the importance of incorporating oral health education into antenatal care (ANC) to enhance maternal knowledge and practices. The study concludes that good maternal oral hygiene can positively influence not only the mother's health but also the long-term oral health of her child. By prioritizing proper dental care during pregnancy, women can help reduce the risk of dental issues in their newborns, contributing to a healthier start in life for future generations.